Tajdid dan Modernisasi Pemikiran Islam - Amal Fathullah Zarkasyi (Universitas Darussalam Gontor, 2013)
Along with development of era, there are many problems of Muslim peoples that did not exist in Prophet’s Era of Muhammad SAW. These problems require an exact and quick solution. One of the media that possible as solution is tajdid and ijtihad. Tajdid is retrieval effort of Islamic doctrine and precepts that have been forgotten or abandoned by Muslims and then reformed to be better. Tajdid is not create some new doctrines in Islam, but restore it to Prophet’s Era of Muhammad SAW and the Four of Caliphs with considering to the situation and condition. Meanwhile, ijtihad is outpouring all powers and abilities to formulating and applying Islamic laws in branch issues and problems that appears in Islamic laws. The problem that occurred is similarization between tajdid’s movement and modernization that affiliated to the western secular tradition. Whereas, the meaning between both of it too different so that brings the different implication if it applied in Islam. The modernization in Islam is a movement to integrated Islam and modern sciences (western). As a consequence, Islam has to adapt its doctrines and principles to what western wants. The effect of this movement will undermine the principles of Islam and induce Muslim people to concede the values of western modernity. Surprisingly, many Muslim scholars using this western’s modernization method into Islamic thought. On the basis of this situation, this paper try to reveals the fundamental differences between tajdid and modernization, and then criticizes the modernization that used by some Muslim scholars.